Reliability of a Portable Fixed Dynamometer During Different Isometric Hamstring Assessments - Ryan Woodbridge; Chloe Ryan; Josh Burkitt; Dana Ye-Lee; John Cronin (Applied Sciences)
Hamstring strain injuries are one of the most common non-contact injuries in sport. Hamstring strength and asymmetry are two key modifiable risk factors for hamstring strain injuries; therefore, it seems important to find reliable tests for assessing hamstring strength. The purpose of this study was to determine the within- and between-session reliability of a portable fixed dynamometer for measuring hamstring strength using three different protocols. Fourteen male participants completed three hamstring isometric protocols across three testing occasions separated by seven days. Peak force, mean force and impulse all had good to excellent within- and between-session reliability for the standing hamstring, supine 90:90 and standing 90:20 assessment (CV = 2.6–11.7%, ICC = 0.74–0.99), while peak rate of force development had moderate to excellent relative consistency (ICC = 0.64–0.90) and unacceptable absolute consistency (CV = 17.1–36.6%). The 90:20 assessment produced significantly higher values (33.4–47.3%) compared to the standing and 90:90 assessments for peak force, mean force and impulse. It appears that a portable fixed dynamometer can reliably measure a range of force–time metrics during three different hamstring assessments; however, the results of the tests cannot be used interchangeably and practitioners comparing hamstring force capability between individuals/research studies need to be cognizant of this and proceed with caution.